Advancements in unsaturated soil mechanics : proceedings of the 3rd GeoMEast International Congress and Exhibition, Egypt 2019 on sustainable civil infrastructures - the official international congress of the Soil-Structure Interaction Group in Egypt (SSIGE) /: proceedings of the 3rd GeoMEast International Congress and Exhibition, Egypt 2019 on sustainable civil infrastructures - the official international congress of the Soil-Structure Interaction Group in Egypt (SSIGE). ([2020]) - Unknown
No abstract available